The importance of groundwater for riverine fish faunas in a region of shale gas development in northern Australia - Davis, Jenny; Garcia, Erica A.; Gibb, Karen S.; Kennard, Mark J.; Rose, Alea; Stromsoe, Nicola; Wedd, Dion (Frontiers in Environmental Science, 2023)
Northern Australia contains the continent’s largest number of intact river systems, but these are facing increasing pressure as the proposed development of multiple and large-scale industries, including onshore gas, mining, horticulture and agriculture, accelerates. These developments will require the diversion or extraction of large amounts of water and increase the risk of contamination by industrial and agricultural chemicals. There is an urgent need to collect baseline biophysical information on these aquatic systems before major developments proceed. Much community concern has been expressed about the potential environmental impacts of a developing shale gas industry (fracking) in the Beetaloo Sub-basin and upper Roper River region of the Northern Territory. Here we describe the results of the first major survey of the freshwater fish fauna of this region and an assessment of the importance of groundwater in supporting fish biodiversity. This region is remote from major human settlements and the waterbodies are often difficult to access. Accordingly, we maximised the information we collected from limited sampling sessions by using both traditional fish survey methods (netting and electrofishing) and eDNA analysis of water and benthic sediment samples. Water column eDNA doubled the number of species recorded to those obtained from traditional survey methods alone. We found that the fish fauna was richest at sites on northward-flowing groundwater-dependent rivers. More work is needed to fully understand the dependence of individual species on groundwater inflows. However, it is evident that conserving freshwater fish biodiversity in these rivers will require protection of the groundwater resources to ensure baseflows and aquatic refuges persist through the most extended of dry seasons.